ANALISIS FINANSIAL USAHA ABON IKAN TUNA (Thunnus sp) PRODUKSI UMKM KOTA PAREPARE - Arman, Arman; Ruslang, Ruslang (Jurnal Pendidikan Teknologi Pertanian, 2017)
Efforts to enhance the value and optimize the utilization of the production of marine catches is to develop value-added products, both traditional and modern processed. One of the many Tuna fish processing done by community group, both home industry and UMKM is abon industry. The abon industry in Parepare city by UMKM "Mekar", involves housewives who work as hired labour, who take advantage of their time and ability to gain added value to Tuna fish that is quite easy to obtain in the market. This study aims to determine the amount of income obtained from the processing of Tuna fish to abon and the feasibility level of UMKM. The data shows the amount of income received by UMKM "Mekar" Parepare in September 2017 is Rp. 141.692.100. The tuna processing business produced in the packaging abon, financially from the R/C ratio = 1.65 is considered feasible to develop.